2014
DOI: 10.4103/1673-5374.125333
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal gene expression in a rat model of depression after electroacupuncture at the Baihui and Yintang acupoints

Abstract: Preliminary basic research and clinical findings have demonstrated that electroacupuncture therapy exhibits positive effects in ameliorating depression. However, most studies of the underlying mechanism are at the single gene level; there are few reports regarding the mechanism at the whole-genome level. Using a rat genomic gene-chip, we profiled hippocampal gene expression changes in rats after electroacupuncture therapy. Electroacupuncture therapy alleviated depression-related manifestations in the model rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…The hippocampus is an important component of the limbic system and regulator of the hypothalamic-pituitary-adrenal (HPA) axis responses that its manipulation by steroid hormones had effect on anxiety and depression [15]. Furthermore, the positive effect of EA on anxiety behaviors via alterations of some molecular pathways in hippocampus in other rat models related to depression, stress, or pain has been shown [1618]. …”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus is an important component of the limbic system and regulator of the hypothalamic-pituitary-adrenal (HPA) axis responses that its manipulation by steroid hormones had effect on anxiety and depression [15]. Furthermore, the positive effect of EA on anxiety behaviors via alterations of some molecular pathways in hippocampus in other rat models related to depression, stress, or pain has been shown [1618]. …”
Section: Introductionmentioning
confidence: 99%
“…[7] Combined with the effect of electrical stimulation, it can produce different treatment effect at different acupoints by adjusting the waveform, time, frequency, and intensity parameters. [8][9][10] Studies showed that treatment with EA could improve cognitive function in patients with Alzheimer disease. [11] Our previous study suggested that preconditioning of EA could reduce the incidence the postoperative cognitive dysfunction in aged rats.…”
Section: Introductionmentioning
confidence: 99%
“…The EA treatment was similar as previously described [19]. EA treatment at Baihui (GV 20, the center of parietal bone) and Yintang (EX-HN3, the middle point of the line between the brow bones) points was conducted for depressed model rats for 28 days (from day 33 to day 59).…”
Section: Methodsmentioning
confidence: 99%